2012
DOI: 10.1177/039463201202500420
|View full text |Cite
|
Sign up to set email alerts
|

Protein Microarrays and Midtrimester Amniotic Fluids: A Novel Approach for the Diagnosis of Early Intrauterine Inflammation Related to Preterm Delivery

Abstract: Novel technologies that allow simultaneous assessment of multiple biomarkers provide new and promising diagnostic/prognostic approaches. By protein microarrays, here we analyzed amniotic fluids (AF) from 50 women with preterm delivery (PTD) and 50 control women, who delivered at term. In detail, cytokines, chemokines, matrix metalloproteinases and antigen-specific antibodies were assessed. The AF analysis showed significant differences between women with preterm and term delivery in the levels of IL-la, IL-lP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…More importantly, this relationship may allow us to accurately identify and possibly intervene in pregnancies at high risk of preterm delivery. Consistent with previous reports which showed the relationship between intra-amniotic infection and/or inflammation in mid-trimester period and subsequent preterm delivery in singleton pregnancies, [9][10][11][12][21][22][23] we also found that elevated levels of immune-related proteins in mid-trimester AF is associated with subsequent risk of early preterm delivery in twin pregnancies. As the AF samples used in this study came from women undergoing clinically indicated amniocentesis for prenatal diagnosis of aneuploidy, these results suggest that the fluid obtained at the time of genetic amniocentesis may be used to assess the risk for preterm delivery in twin gestations.…”
Section: Strengths and Limitationssupporting
confidence: 92%
See 1 more Smart Citation
“…More importantly, this relationship may allow us to accurately identify and possibly intervene in pregnancies at high risk of preterm delivery. Consistent with previous reports which showed the relationship between intra-amniotic infection and/or inflammation in mid-trimester period and subsequent preterm delivery in singleton pregnancies, [9][10][11][12][21][22][23] we also found that elevated levels of immune-related proteins in mid-trimester AF is associated with subsequent risk of early preterm delivery in twin pregnancies. As the AF samples used in this study came from women undergoing clinically indicated amniocentesis for prenatal diagnosis of aneuploidy, these results suggest that the fluid obtained at the time of genetic amniocentesis may be used to assess the risk for preterm delivery in twin gestations.…”
Section: Strengths and Limitationssupporting
confidence: 92%
“…Approximately one third of all cases of preterm labor or preterm premature rupture of membranes show evidence of intra-amniotic infection and/or inflammation, and the presence of intra-amniotic infection and/or inflammation during pregnancy is strongly correlated with the risk of preterm delivery and adverse neonatal outcome. [3][4][5][6][7][8] Recent studies have shown that elevated biomarkers of intraamniotic infection and/or inflammation in the mid-trimester period in otherwise uncomplicated and asymptomatic pregnancies are associated with an increased risk of subsequent preterm delivery in singleton gestations, [9][10][11][12] although not all investigators were able to demonstrate this association. 13,14 However, there is a paucity of information regarding the relationship between biomarkers of inflammation in mid-trimester amniotic fluid (AF) and the risk of subsequent preterm delivery in twins.…”
Section: Introductionmentioning
confidence: 99%
“…The quantification of each cytokine/chemokine was achieved by interpolating the fluorescent signals to the standard curve, generated by processing some arrays with specific standards, containing predetermined cytokines concentrations (pg/mL) . hBTSC were exposed to 1 μg/mL lipopolysaccharides to check the capability of these cells to secrete cytokines and to detect them with this array.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, AF may also be a promising medium for the identification of candidate markers of adverse perinatal outcomes, specifically PTB. AF proteins include cytokines, chemokines, matrix metalloproteinases and antigen-specific antibodies, potentially involved in the mechanisms leading to PTB (La Sala et al, 2012). From the perspective of peptide-content, AF is thought to mimic fetal plasma during 10 to 20 weeks of gestation (Cho et al, 2007).…”
Section: Biomarkers In Af For Early Detection Of Spontaneous Preterm mentioning
confidence: 99%
“…These markers include cytokines, chemokines, matrix metalloproteinases, and antigen-specific antibodies that have been used to diagnose early intrauterine inflammation leading to PTB (La Sala et al, 2012). Putative PTB biomarkers can be grouped according to type of mechanism, including inflammation, placental proteins/hormonal, angiogenesis, or coagulation (Conde-Agudelo et al, 2011); these are discussed individually below.…”
Section: The Diagnostic Value Of Proteins In Amniotic Fluidmentioning
confidence: 99%